Cinta Tzu Chi 2 Muara Angke flat is one of some alternative home to people especially fishermen who lived in Kali Adem riverbank. Develop the flat sponsored by Budha Tzu Chi Foundation. How the attitude's people to live in this flat is important to know, so the aim of this research were: to know how level of their attitude to live in this flat, to identify of factors that correlate with attitude, and the fit of the attitude with behaviour to live in this flat. The result of research showed - Diyah Anggraeni; Yatri Indah K; Anna Fatchiya (Buletin Ekonomi Perikanan, 2007)
Cinta Tzu Chi 2 Muara Angke flat is one of some alternative home to people especially fishermen who lived in Kali Adem riverbank. Develop the flat sponsored by Budha Tzu Chi Foundation. How the attitude's people to live in this flat is important to know, so the aim of this research were: to know how level of their attitude to live in this flat, to identify of factors that correlate with attitude, and  the fit of the attitude with behaviour to live in this flat. The result of research showed that (1) the attitude's people to live in this flat was in the good level, their reason was live in the flat is better than live in the riverbank, (2) The internal factor was the floor level of the flat and the external factors were the rules of conduct from Cinta Kasih Tzu Chi 2 management and the conditions of their house when they have been lived in riverbank those influenced attitue'people to live in this flat, (3) There were positif or negatif correlation between the attitude with behaviour in the people who live in this flat. The positif correlations were on the domestic activities (children carieng, family gathering), rule of conduct (paying of bill) and social activities (freedom to activities), another side the negative correlation are on domestic activities (keeping of cleaning and good looking of the flat environment)